2014
DOI: 10.1002/rrq.89
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Awareness in Vocabulary Acquisition Among Chinese‐Speaking Children: Testing Partial Mediation via Lexical Inference Ability

Abstract: The goal of this study was to investigate the effect of Chinese‐specific morphological awareness on vocabulary acquisition among young Chinese‐speaking students. The participants were 288 Chinese‐speaking second graders from three different cities in China. Multiple regression analysis and mediation analysis were used to uncover the mediated and unmediated effects of morphological awareness on reading vocabulary knowledge. Results showed that both morphological awareness and lexical inference ability significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 56 publications
6
46
0
3
Order By: Relevance
“…However, compound awareness was not found to have a signifi cant eff ect on English vocabulary depth. Recent studies confi rmed that cross-linguistic compound awareness in both Chinese and English significantly contributed to Chinese vocabulary knowledge (e.g., Chen et al, 2009;Liu & McBride-Chang, 2010;Pasquarella, Chen, Lam, Luo, & Ramirez, 2011;Zhang, 2015) and cross-linguistic derivational awareness was found to significantly predict English vocabulary development (Kieffer & Lesaux, 2012;Zhang, 2013). The current study also justified that there were cross-linguistic variations of morphological awareness in vocabulary development, and English compound awareness was a weaker predictor of ESL vocabulary knowledge compared with English derivational awareness.…”
Section: Discussion and Conclusion The Role Of Derivational Awarenesssupporting
confidence: 78%
See 1 more Smart Citation
“…However, compound awareness was not found to have a signifi cant eff ect on English vocabulary depth. Recent studies confi rmed that cross-linguistic compound awareness in both Chinese and English significantly contributed to Chinese vocabulary knowledge (e.g., Chen et al, 2009;Liu & McBride-Chang, 2010;Pasquarella, Chen, Lam, Luo, & Ramirez, 2011;Zhang, 2015) and cross-linguistic derivational awareness was found to significantly predict English vocabulary development (Kieffer & Lesaux, 2012;Zhang, 2013). The current study also justified that there were cross-linguistic variations of morphological awareness in vocabulary development, and English compound awareness was a weaker predictor of ESL vocabulary knowledge compared with English derivational awareness.…”
Section: Discussion and Conclusion The Role Of Derivational Awarenesssupporting
confidence: 78%
“…In this sense, sensitivity to morpheme knowledge is crucial to meaning construction in vocabulary learning. Many studies have found the positive relationship between morphological awareness and vocabulary knowledge among monolingual speakers of different language backgrounds (e.g., Chen, Hao, Geva, Zhu, & Shu, 2009;Ku & Anderson, 2003;Liu & McBride-Chang, 2010;McBride-Chang, Wagner, Muse, Chow, & Shu, 2005;Zhang, 2015).…”
Section: Morphological Awareness and English Vocabulary Knowledgementioning
confidence: 99%
“…There is a growing consensus that they are indeed distinguishable skills. For instance, several cross‐sectional studies have shown morphological awareness and morphological analysis to be positively correlated in children and adults but not redundantly or overly correlated, as would be expected if multicollinearity was an issue (e.g., Deacon et al., ; D. Zhang & Koda, ; H. Zhang, ). Confirmatory factor analysis has also demonstrated that morphological awareness and morphological analysis are best represented as separate constructs rather than a single morphology construct for students in grades 3 (Levesque et al., ), 7, and 8 (Goodwin et al., ).…”
Section: Empirical Research On the Developmental Relation Between Mormentioning
confidence: 93%
“…Although morphological analysis can be applied strategically to understand words, we view it as a form of online, tacit morphological processing (see Goodwin, Petscher, Carlisle, & Mitchell, ). In research, this construct is most often measured by asking students to choose or produce definitions for multimorphemic words (e.g., McCutchen & Logan, ; Pacheco & Goodwin, ; H. Zhang, ). Critically, the distinction between these morphological constructs has not always been clear in empirical research (e.g., Carlisle & Fleming, ; McBride‐Chang, Wagner, Muse, Chow, & Shu, ).…”
mentioning
confidence: 99%
“…Reading acquisition is a very complex process because it necessitates fundamental semantic meaning activation at both the local word level and the global text level [4]. Reading researchers have shown that word learning and reading development benefit from a wide variety of cognitive and linguistic abilities (e.g., working memory, metacognitive strategies, word reading, lexical inference) [5,6]. The existing literature has extensively focused on the correlation between various indicators and reading outcomes, which lack an in-depth understanding of how various factors can contribute to actual instruction and learning.…”
Section: Introductionmentioning
confidence: 99%